2015
DOI: 10.1002/dac.2970
|View full text |Cite
|
Sign up to set email alerts
|

A simple design of planar microstrip antenna on composite material substrate for Ku/K band satellite applications

Abstract: A straight forward design of rectangular slotted microstrip planar antenna fed by 50 ohm microstrip line is proposed for Ku/K band satellite applications. The radiating patch of the antenna occupies an area of 17 × 17 mm 2 and fabricated on 1.0 mm-thick ceramic filled bioplastic composite material substrate whose dielectric constant (ε r ) is 10.0. The dual resonant square-shaped antenna has been formed by inserting four arc shape slots at the corners with the combination of circle and square and wide square s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…From the perusal of Table , it is clear that the total volume of the proposed antenna is greater as compared to the antennas reported in Refs. by a factor of 4.38, 1.17, and 1.95, respectively, whereas it occupies lesser volume than antennas reported in Refs. by a factor of 4.7 and 1.11, respectively.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…From the perusal of Table , it is clear that the total volume of the proposed antenna is greater as compared to the antennas reported in Refs. by a factor of 4.38, 1.17, and 1.95, respectively, whereas it occupies lesser volume than antennas reported in Refs. by a factor of 4.7 and 1.11, respectively.…”
Section: Introductionmentioning
confidence: 65%
“…Since last few years, researchers have been investigating the implementation of the patch antennas in Ku/K band for satellite and radar applications but are still struggling to obtain the optimum structure with high gain and sufficient bandwidth. In order to obtain the compact structure with improved gain and radiation characteristics in the Ku/K band applications, different configurations of patch antenna structures have been reported by researchers . In this work, a compact dual‐wideband semi‐circular (substrate and patch both) shape micro‐strip patch antenna is presented for Ku/K band applications.…”
Section: Introductionmentioning
confidence: 67%
“…It may be observed that the radiation patterns at all these frequencies are stable and maximum radiations are directed normal to the patch geometry. The antenna could serve as a potential candidate for Ku band of satellite communication and other suitable applications having better radiation performance as compared to the recently reported works [14][15][16]. …”
Section: Simulation Resultsmentioning
confidence: 96%
“…In Reference , a compact wideband antenna for Ku‐band satellite communication applications was reported. Its operating band was enhanced by using four arcs and a square slot to use it for Ku‐band and K‐band satellite applications …”
Section: Introductionmentioning
confidence: 99%